Nano-copper metal material for low-temperature sintering conductive paste and preparation and application of paste of nano-copper metal material

Nanocopper particles and nanowires were prepared hydrothermal by one-step method and mixed with organic solvents and small-molecular organic copper salts, which solved the problems of high sintering temperature and complex preparation process of existing copper slurry, and realized the preparation of low-temperature sintered conductive paste , improves the density and performance of the bonding layer.

CN119418979APending Publication Date: 2025-02-11EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411506400.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing copper slurry has a high sintering temperature, complex preparation process and non-density sintering, resulting in low bonding strength and cannot meet the mechanical requirements of bonding silicon carbide power device chips and substrates.

Method used

Nanocopper particles and nanowires were prepared by one-step hydrothermal method, and copper nanoparticles were formed by adjusting pH value and heating conditions. The reduction agent and capping agent were used to achieve the directional growth of nanowires, and mixed with organic solvents and small-molecular organic copper salts. , low-temperature sintered conductive paste was prepared.

Benefits of technology

The preparation of low-temperature sintered conductive paste is realized, the sintering temperature is reduced, the density and performance of the bonding layer is improved, and the bonding requirements of silicon carbide power devices are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119418979A_ABST
    Figure CN119418979A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electronic packaging, and relates to a nano-copper metal material for low-temperature sintering conductive paste and preparation and application of the paste of the nano-copper metal material. The nano-copper metal material comprises copper nanoparticles and copper nanowires, and the copper nanoparticles and the copper nanowires are both prepared through a one-step hydrothermal method: (1) the copper nanoparticles are prepared, specifically, the high-purity copper nanoparticles are obtained through a hydrothermal reaction by adjusting the pH value; (2) preparing a copper nanowire: carrying out hydrothermal reaction on a copper source, a reducing agent and an end-capping reagent, so that copper ions are reduced into quintuple twin crystal seeds in one step and further directionally deposited into the copper nanowire; and (3) preparing conductive paste: mixing the nano-copper material and an organic reagent according to a certain proportion, and homogenizing to obtain the low-temperature sintering type conductive copper paste. The low-temperature copper paste is used for preparing the low-temperature copper paste for bonding a chip and a substrate. The prepared nano-copper metal material for the low-temperature sintering conductive paste is stable in size and simple in preparation process, and the prepared paste is good and excellent in sintering performance (the shear strength is 25 MPa, and the thermal conductivity is 4 W / m.K).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic packaging, and in particular relates to a nano copper metal material for low-temperature sintering conductive paste and the preparation and application of the paste. Background Art

[0002] In contemporary society, semiconductor technology has achieved rapid progress and wide application, especially in the field of power devices. Taking silicon carbide power devices as an example, they not only lead the industry innovation, but also show wide application in the field of new energy vehicles. A single vehicle contains more than 100 application scenarios, highlighting its increasing importance in the industrial and civilian fields. In silicon carbide power devices, bonding and sealing materials and technologies play a core role, directly determining the performance of the device, especially in extreme environments. At present, although high-lead solder occupies a dominant position in the market, it is limited by the disadvantages of low melting point and rapid performance decay at high temperature. Silver paste, with its excellent electrical conductivity, thermal conductivity and durability, provides high-quality bonding and sealing solutions for silicon carbide power devices, but the high cost and electromobility issues restrict its possibility of popularization. Recently, copper paste is gradually becoming the focus of industry attention due to its cost-effectiveness, abundant resource reserves, environmental friendliness, better thermal cycling ability, and conductivity and lower electromobility comparable to silver paste, indicating that it has broad application prospects in the field of bonding and sealing of silicon carbide power devices.

[0003] Traditional copper paste can be divided into high-temperature sintering copper-based conductors and low-temperature curing copper-based conductors. However, the paste used for bonding chips to DBC ceramic substrates or AMB copper substrates must meet the requirements of low sintering temperature and high bonding strength at the same time. Since the curing temperature of low-temperature curing copper-based conductors is too low, a strongly linked sintering neck cannot be formed between the copper particles, causing cracking and brittleness of the copper film, which seriously reduces the strength of the bonding layer and cannot meet the mechanical requirements for bonding silicon carbide power device chips to DBC ceramic substrates or AMB copper substrates. At the same time, traditional sintering copper pastes usually require densification sintering between 600°C and 900°C to achieve strong sintering bonding, which far exceeds the requirement that chip packaging cannot exceed 300°C. To this end, studies have found that adding nanosilver particles or pressurizing high-temperature sintered silver-based conductors can achieve the needs of low-temperature sintering and high-strength bonding. Based on the above research foundation, copper powder can be nano-sized to increase the surface activity of the powder, reduce the sintering temperature, and add nanowires to increase the packing density of copper powder, thereby efficiently improving the density of the sintered layer to improve mechanical, electrical and thermal properties. Patent application CN105567808B discloses a method for synthesizing copper nanoparticles using rolling circle amplification products as templates. Copper nanoparticles were synthesized using DNA with polythymine repeat sequences as templates, which solved the problem of expensive equipment, but there are still problems of complex processes and difficult control. Patent application CN114068957A discloses a method for preparing a graphene-supported PtCu nanodendritic catalyst. First, copper nanoparticles are prepared in a two-step method under wet nitrogen conditions using ascorbic acid and sodium borohydride as reducing agents for the next step of synthesis, which solves the problem of complex process, but the reducing agent sodium borohydride is easy to explode. Patent application CN113362984A discloses a nanoparticle copper paste suitable for high-precision direct writing 3D printing. Triaryl phosphine and trialkyl phosphine compounds are used as reducing agents and copper nanoparticles are added to solve the problem of reducing agent safety, but there are still problems such as not being able to be made in one step and not being applicable to nano copper materials of other dimensions. The preparation process and materials for the above problems need to be further optimized.

[0004] Therefore, it is necessary to provide a nano copper metal material for low-temperature sintering conductive paste that is of suitable size, simple to prepare, and densely sintered, and then use it to produce a silicon carbide power device with a chip-substrate structure with a reliable connection. Summary of the invention

[0005] In order to solve the above-mentioned problems such as high sintering temperature, complex preparation process, loose sintering, and low bonding strength, the present invention provides a nano copper metal material for low-temperature sintering conductive paste with suitable size, simple preparation, and dense sintering, and the preparation and application of its paste.

[0006] The nano copper metal material for low temperature sintering conductive paste of the present invention includes copper nanoparticles and copper nanowires. Although the above materials are all prepared by one-step hydrothermal method, the formation process is different. Copper nanoparticles are formed according to the path of divalent copper source-copper hydroxide-cuprous oxide-copper. First, the divalent copper is converted into copper hydroxide by adjusting the pH to form an alkaline environment; then the reducing ability of the reducing agent is used to form cuprous oxide; finally, while maintaining the alkaline conditions, it is heated to a certain temperature to form a copper element. As for the copper nanowire, it first obtains a five-fold twin copper seed by relying on the reducing ability of the reducing agent, and then the selective capping ability of the capping agent is used to make the copper seed grow in a directional manner. The nano size is achieved by using a capping agent and a dispersant. The obtained nano copper material has a small size, good shape, and excellent performance, and can well adapt to the use requirements of low temperature sintering conductive copper paste. The prepared nano copper material is mixed with a small molecule organic copper salt and its corresponding small molecule organic reagent dissolved in an organic solvent at a certain temperature in a certain proportion to obtain a low-temperature sintering conductive slurry, which is further applied to the bonding layer between the chip and the DBC ceramic substrate or the AMB copper substrate.

[0007] The invention has simple synthesis and low equipment requirements. Compared with the mainstream preparation methods on the market, the invention is a preparation method of nano copper metal materials for low-temperature sintering conductive paste that is more cost-effective and suitable for promotion. The preparation can be scaled up, and the size of the nano material can be adjusted by adjusting the process parameters. The material shows excellent performance in low-temperature sintering conductive paste. The compounding of nanoparticles and nanowires can greatly enhance the sintering density and provide good mechanical and electrothermal properties, thereby being better suitable for bonding the chip to the DBC ceramic substrate or the AMB copper substrate.

[0008] The specific technical solution adopted by the present invention is as follows:

[0009] One of the purposes of the present invention is to provide a method for preparing nano copper metal particles for low temperature sintering conductive paste, which specifically comprises the following steps:

[0010] (1) Weighing a copper source, a reducing agent, and a dispersing agent, dissolving them in deionized water; stirring evenly, performing a hydrothermal reaction, and cooling naturally; and obtaining a copper nanoparticle precursor.

[0011] (2) The precursor is washed and centrifuged to obtain a precipitate, namely, copper nanoparticles.

[0012] Furthermore, in step (1), the copper source is one or more of copper sulfate pentahydrate, copper chloride dihydrate, and copper nitrate trihydrate; the reducing agent is one or more of glucose, ascorbic acid, and sodium citrate; and the dispersant is one or more of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol. The following is an example in which the copper source, the reducing agent, and the dispersant are copper sulfate pentahydrate, glucose, and polyvinyl pyrrolidone, respectively.

[0013] Furthermore, in step (1), the mass ratio of copper sulfate pentahydrate, glucose, polyvinyl pyrrolidone and deionized water is (5-65) g: (8-95) g: (5-60) g: (80-1500) g; the temperature of the hydrothermal reaction is 60-90° C., and the time of the hydrothermal reaction is 1-3 h.

[0014] Furthermore, the washing reagents are acetone and alcohols, the alcohols are ethanol or isopropanol; the solubility ratio of the acetone and alcohol solutions is (10-20) ml: (30-40) ml.

[0015] The second object of the present invention is to provide a method for preparing nano copper metal wire for low temperature sintering conductive paste, which specifically comprises the following steps:

[0016] (1) Weigh a copper source, a reducing agent, and a capping agent, and dissolve them in deionized water; stir evenly, perform a hydrothermal reaction, and cool naturally; and obtain a copper nanoparticle precursor.

[0017] (2) The precursor is washed and centrifuged to obtain a precipitate, namely, copper nanowires.

[0018] Furthermore, in step (1), the copper source is one or more of copper sulfate pentahydrate, copper chloride dihydrate, and copper nitrate trihydrate; the reducing agent is one or more of glucose, ascorbic acid, and sodium citrate; and the dispersant is one or more of tetradecylamine, hexadecylamine, and octadecylamine. The following is an example in which the copper source, the reducing agent, and the dispersant are copper chloride dihydrate, glucose, and hexadecylamine, respectively.

[0019] Furthermore, in step (1), the mass ratio of copper chloride dihydrate, glucose, hexadecylamine and deionized water is (5.545-55.45) g: (5.86-58.6) g: (7.85-70.63) g: (500-1500) g; the temperature of the hydrothermal reaction is 120-200° C., and the time of the hydrothermal reaction is 8-40 h.

[0020] Furthermore, the washing reagents are acetone and alcohols, the alcohols are ethanol or isopropanol; the solubility ratio of the acetone and alcohol solutions is (10-20) ml: (30-40) ml.

[0021] The third purpose of the present invention is to provide the application of the above-mentioned nano copper metal material for low-temperature sintering conductive paste. The prepared nano copper material is mixed with a small molecule organic copper salt and its corresponding small molecule organic reagent dissolved in an organic solvent at a certain temperature in a certain proportion to obtain a low-temperature sintering conductive paste. As a bonding material between semiconductor chips and DBC ceramic substrates or AMB copper substrates, the material can provide a reliable and durable bonding layer, and is used in the manufacturing of electronic products such as silicon carbide power devices, printed circuit boards, MLCCs and automotive electronics. This material is used in the semiconductor field and has the advantages of low bonding temperature and good sintering performance: it can be sintered at 200-400°C and obtain relatively good bonding performance - high density, high thermal conductivity, low porosity and high temperature stability.

[0022] Furthermore, the organic solvent is dimethylformamide and dimethyl sulfoxide, the small molecule organic copper salt is copper formate and copper acetate; the small molecule organic reagent is formic acid and acetic acid; the dissolution temperature is 40-150°C; the mass ratio of the nano-copper material, the organic solvent, the small molecule organic copper salt, and the small molecule organic reagent is 80:15:4.5:0.5; the nano-copper material is nanoparticles and nanowires; the molar ratio of the nanoparticles and nanowires is (3-4) mol: (1-2) mol.

[0023] The present invention has the following beneficial effects:

[0024] 1. The size of the material of the present invention reaches the nanometer level, and the size is appropriate, which can effectively reduce the sintering temperature of the copper paste and improve the performance of the bonding layer.

[0025] 2. The synthesis method of the present invention is simple and can be mass-produced, eliminating the need for expensive equipment and avoiding the problem of excessively high costs. A nano copper metal material for low-temperature sintering conductive paste is successfully synthesized, which is a new type of electronic sealing material with excellent performance.

[0026] 3. The bonding layer obtained by the present invention has high density, high shear strength and high thermal conductivity, and fully meets the bonding requirements between the chip and the DBC ceramic substrate or the AMB copper substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The figure is a schematic diagram of the synthesis process of the nanomaterial for low-temperature copper paste of the present invention.

[0028] Figure 2 The X-ray diffraction spectra of the nanomaterials for low-temperature copper paste prepared in Example 1 and Example 4.

[0029] Figure 3 The scanning electron microscope images of the nanoparticles and nanowires for low-temperature copper paste prepared in Example 1, Example 2, Example 4, and Example 5 are shown. DETAILED DESCRIPTION

[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The described embodiments are only part of the embodiments of the invention. Other embodiments obtained by ordinary technicians in this field based on the present invention are also covered within the protection scope of the present invention.

[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0032] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0033] Example 1

[0034] Preparation of CuNP-1 nanoparticles for low temperature sintering conductive paste (process as shown in Figure 1 a).

[0035] First, 31.25 g of copper sulfate pentahydrate and 14.5 g of polyvinyl pyrrolidone were weighed and dissolved in 250 ml of deionized water, and magnetic stirring was performed for 30 minutes to disperse, thereby obtaining solution A.

[0036] 45.04 g of glucose and 14.5 g of polyvinyl pyrrolidone were weighed and dissolved in 250 ml of deionized water, and magnetically stirred for 30 min to disperse, thereby obtaining solution B.

[0037] Heat solution B to 85°C and maintain a stirring speed of 350r; drip solution A into solution B at a certain speed during the heating process.

[0038] After the titration is completed, the 5 mol / L NaOH prepared in advance is titrated into the mixed solution at a certain speed until the pH is 10, and the pH value is remeasured every five minutes. The pH value of the reaction solution is always kept equal to 10 by titration of NaOH. The reaction is carried out for 1 hour; the solution changes from blue-green-yellow-orange-red.

[0039] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNP was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0040] The prepared CuNP-1 and CuNW-1 were mixed in a mass ratio of 4:1, that is, 12.8 g of CuNP-1 and 3.2 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0041] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0042] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0043] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0044] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 120° C. for drying for 10 min.

[0045] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 300°C at 5°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0046] The device was tested for performance. The results showed that the bonding layer was sintered densely, with a shear strength of up to 25MPa and a thermal conductivity of up to 4W / m·K.

[0047] Example 2

[0048] Preparation of CuNP-2 nanoparticles for low temperature sintering conductive paste (process as shown in Figure 1 a).

[0049] First, 62.5 g of copper sulfate pentahydrate and 29 g of polyvinyl pyrrolidone were weighed and dissolved in 500 ml of deionized water, and magnetic stirring was applied for 35 minutes to disperse the mixture, thereby obtaining solution A.

[0050] 90.08 g of glucose and 29 g of polyvinyl pyrrolidone were weighed and dissolved in 500 ml of deionized water, and magnetically stirred for 35 min to disperse, thereby obtaining solution B.

[0051] Heat solution B to 80°C and maintain a stirring speed of 350r; drip solution A into solution B at a certain speed during the heating process.

[0052] After the titration is completed, the 5 mol / L NaOH prepared in advance is titrated into the mixed solution at a certain speed until the pH is 10, and the pH value is remeasured every five minutes. The pH value of the reaction solution is always kept equal to 10 by titration of NaOH. The reaction is carried out for 2 hours; the solution changes from blue-green-yellow-orange-red.

[0053] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNP was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0054] The prepared CuNP-2 and CuNW-1 were mixed in a mass ratio of 4:1, that is, 12.8 g of CuNP-1 and 3.2 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0055] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0056] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0057] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0058] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 120° C. for drying for 10 min.

[0059] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 300°C at 5°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0060] The device was tested for performance. The results showed that the bonding layer was sintered densely, with a shear strength of up to 23MPa and a thermal conductivity of up to 3.7W / m·K.

[0061] Example 3

[0062] Preparation of CuNP-3 nanoparticles for low temperature sintering conductive paste (process as shown in Figure 1 a).

[0063] First, 62.5 g of copper sulfate pentahydrate and 29 g of polyvinyl pyrrolidone were weighed and dissolved in 500 ml of deionized water, and magnetic stirring was applied for 40 minutes to disperse the mixture, thereby obtaining solution A.

[0064] 90.08 g of glucose and 29 g of polyvinyl pyrrolidone were weighed and dissolved in 500 ml of deionized water, and magnetic stirring was performed for 40 minutes to disperse the mixture, thereby obtaining solution B.

[0065] Heat solution B to 90°C and maintain a stirring speed of 350r; drip solution A into solution B at a certain speed during the heating process.

[0066] After the titration is completed, the 5 mol / L NaOH prepared in advance is titrated into the mixed solution at a certain speed until the pH is 10, and the pH value is remeasured every five minutes. The pH value of the reaction solution is always kept equal to 10 by titration of NaOH. The reaction is carried out for 3 hours; the solution changes from blue-green-yellow-orange-red.

[0067] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNP was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0068] The prepared CuNP-3 and CuNW-1 were mixed in a mass ratio of 4:1, that is, 12.8 g of CuNP-1 and 3.2 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0069] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0070] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0071] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0072] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 120° C. for drying for 10 min.

[0073] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 300°C at 5°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0074] The device was tested for performance. The results showed that the bonding layer was sintered densely, with a shear strength of up to 24MPa and a thermal conductivity of up to 3.8W / m·K.

[0075] Example 4

[0076] Preparation of CuNW-1 nanowires for low temperature sintering conductive paste (flow chart as shown in Figure 1 b).

[0077] First, weigh 5.545 g of copper chloride dihydrate and 39.24 g of hexadecylamine, dissolve them in 500 ml of deionized water, and disperse them by ultrasonic treatment for five minutes; weigh 5.86 g of glucose, add it to the above solution, and stir for 12 hours.

[0078] The solution stirred into a colloid was placed in the inner lining of a hydrothermal autoclave and maintained at 120°C for 8 h.

[0079] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNW was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0080] The prepared CuNP-1 and CuNW-1 were mixed in a mass ratio of 2:1, that is, 10.7 g of CuNP-1 and 5.3 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0081] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0082] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0083] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0084] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 120° C. for drying for 10 min.

[0085] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 275°C at a rate of 10°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0086] The device was tested for performance. The results showed that the bonding layer was sintered densely, with a shear strength of up to 22MPa and a thermal conductivity of up to 3.2W / m·K.

[0087] Example 5

[0088] Preparation of CuNW-2 nanowires for low temperature sintering conductive paste (flow chart as shown in Figure 1 b).

[0089] First, weigh 5.545 g of copper chloride dihydrate and 31.39 g of hexadecylamine, dissolve them in 500 ml of deionized water, and disperse them by ultrasonic for five minutes; weigh 5.86 g of glucose, add it to the above solution, and stir for 12 hours.

[0090] The solution stirred into a colloid was placed in the inner lining of a hydrothermal autoclave and maintained at 120°C for 10 h.

[0091] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNW was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0092] The prepared CuNP-1 and CuNW-2 were mixed in a mass ratio of 4:1, that is, 12.8 g of CuNP-1 and 3.2 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0093] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0094] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0095] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0096] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 120° C. for drying for 10 min.

[0097] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 350°C at a rate of 10°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0098] The device was tested for performance. The results showed that the bonding layer was sintered densely, with a shear strength of up to 24MPa and a thermal conductivity of up to 3.8W / m·K.

[0099] Example 6

[0100] Preparation of CuNW-3 nanowires for low temperature sintering conductive paste (flow chart as shown in Figure 1 b).

[0101] First, weigh 5.545 g of copper chloride dihydrate and 23.545 g of hexadecylamine, dissolve them in 500 ml of deionized water, and disperse them by ultrasonic for five minutes; weigh 5.86 g of glucose, add it to the above solution, and stir for 12 hours.

[0102] The solution stirred into a colloid was placed in the inner lining of a hydrothermal autoclave and maintained at 120°C for 12 h.

[0103] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNW was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0104] The prepared CuNP-1 and CuNW-3 were mixed in a mass ratio of 4:1, that is, 12.8 g of CuNP-1 and 3.2 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0105] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0106] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0107] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0108] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 140° C. for drying for 10 min.

[0109] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 300°C at 5°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0110] The device was tested for performance. The results showed that the bonding layer was sintered densely, with a shear strength of up to 23MPa and a thermal conductivity of up to 3.5W / m·K.

[0111] Example 7

[0112] Preparation of CuNW-4 nanowires for low temperature sintering conductive paste (flow chart as shown in Figure 1 b).

[0113] First, weigh 5.545 g of copper chloride dihydrate and 47.09 g of hexadecylamine, dissolve them in 800 ml of deionized water, and disperse them by ultrasonic treatment for five minutes; weigh 5.86 g of glucose, add it to the above solution, and stir for 12 hours.

[0114] The solution stirred into a colloid was placed in the inner lining of a hydrothermal autoclave and maintained at 120°C for 8 h.

[0115] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNW was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0116] The prepared CuNP-1 and CuNW-4 were mixed in a mass ratio of 4:1, that is, 12.8 g of CuNP-1 and 3.2 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0117] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0118] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0119] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0120] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 120° C. for drying for 10 min.

[0121] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 300°C at 15°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0122] The device was tested for performance. The results showed that the bonding layer was sintered densely, with a shear strength of up to 22MPa and a thermal conductivity of up to 3.2W / m·K.

[0123] Example 8

[0124] Preparation of CuNW-5 nanowires for low temperature sintering conductive paste (flow chart as shown in Figure 1 b).

[0125] First, weigh 5.545 g of copper chloride dihydrate and 54.935 g of hexadecylamine, dissolve them in 800 ml of deionized water, and disperse them by ultrasonic for five minutes; weigh 5.86 g of glucose, add it to the above solution, and stir for 12 hours.

[0126] The solution stirred into a colloid was placed in the inner lining of a hydrothermal autoclave and maintained at 120°C for 8 h.

[0127] Then, the obtained crude liquid was placed in a centrifuge tube and centrifuged at 9000r for 8 minutes. After the first centrifugation, the supernatant was poured out, ethanol and acetone were added, and the mixture was dispersed in an ultrasonic machine. The above operation was repeated until the supernatant was clear. Finally, half of the obtained CuNW was placed in a vacuum oven for drying, and the other half was added with isopropanol for later use.

[0128] The prepared CuNP-1 and CuNW-5 were mixed in a mass ratio of 4:1, that is, 12.8 g of CuNP-1 and 3.2 g of CuNW-1 were weighed, and the two were redissolved in 10 ml of isopropanol to obtain a C solution.

[0129] Weighed 0.9 g of copper formate and 0.1 g of formic acid were dissolved in 3 g of dimethylformamide at 60°C to obtain solution D.

[0130] The C and D solutions were mixed, placed in a mixing and degassing machine and homogenized at a rate of 1200r (30s) - 1800r (40s) - 1000r (30s) to obtain E slurry.

[0131] The E slurry is further ground by a three-roll mill to obtain the final low-temperature sintered conductive copper slurry.

[0132] The obtained low-temperature sintered conductive copper paste was screen-printed onto the AMB copper substrate, and the chip was attached to the other side of the copper paste and placed in a forced air oven at 120° C. for drying for 10 min.

[0133] The dried chip-copper paste-AMB copper substrate structure was placed in a tube furnace, and heated to 275°C at 5°C / min in a nitrogen atmosphere and kept at this temperature for 30 minutes.

[0134] The device was tested for performance, and the results showed that the bonding layer was sintered densely, with a shear strength of up to 23MPa and a thermal conductivity of up to 3.8W / m·K.

[0135] Performance Testing

[0136] The microscopic morphology and curing performance of the nanomaterials for low-temperature curing conductive paste in the above embodiment - density was characterized by a Talos F200X field emission transmission electron microscope. The X-ray diffraction spectrum was measured by a D8 Advance ECO small angle XRD instrument. The shear strength was measured by an MTS Criterion Model 45 tensile tester. The thermal conductivity was measured by an LFA 1000 laser thermal conductivity instrument.

[0137] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A nano copper metal material for low temperature sintering conductive paste, characterized in that: It includes copper nanoparticles and copper nanowires; wherein the copper nanoparticles are spherical copper with a particle size of 200-400nm; the copper nanowires loaded by the particles are quintuple twin nanowires with a diameter of 50-100nm and a length of 2-3μm.

2. A method for preparing the nano copper metal particles for low temperature sintering conductive paste according to claim 1 by one-step hydrothermal method, characterized in that: The following steps are involved: (1) Weigh a copper source, a reducing agent, and a dispersant, dissolve them in deionized water, stir evenly, perform a hydrothermal reaction, and cool naturally to obtain a copper nanoparticle precursor, wherein the copper source is one or more of copper sulfate pentahydrate, copper chloride dihydrate, and copper nitrate trihydrate; the reducing agent is one or more of glucose, ascorbic acid, and sodium citrate; and the dispersant is one or more of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol. (2) Washing the precursor of step (1) and obtaining a precipitate by centrifugal separation, namely copper nanoparticles, wherein the washing reagents are acetone and alcohol, the alcohol is ethanol or isopropanol; and the volume ratio of acetone to alcohol solution is (10-20) ml: (30-40) ml.

3. The method for preparing nano copper metal particles for low temperature sintering conductive paste according to claim 2, characterized in that: In step (1), the mass ratio of the copper source, the reducing agent, the dispersant and the deionized water is (5-65) g: (8-95) g: (5-60) g: (80-1500) g; the temperature of the hydrothermal reaction is 60-90° C., and the time of the hydrothermal reaction is 1-3 h.

4. The method for preparing a nano copper metal wire for low temperature sintering conductive paste as claimed in claim 1, characterized in that: The following steps are involved: (1) Weighing a copper source, a reducing agent, and a capping agent, dissolving them in deionized water; stirring evenly, performing a hydrothermal reaction, and cooling naturally; obtaining a copper nanowire precursor, wherein the copper source is one or more of copper sulfate pentahydrate, copper chloride dihydrate, and copper nitrate trihydrate; the reducing agent is one or more of glucose, ascorbic acid, and sodium citrate; and the dispersing agent is one or more of tetradecylamine, hexadecylamine, and octadecylamine. (2) Washing the precursor of step (1) and obtaining a precipitate by centrifugal separation, namely copper nanowires, wherein the washing reagents are acetone and alcohol, and the alcohol is ethanol or isopropanol; and the volume ratio of the acetone and alcohol solution is (10-20) ml: (30-40) ml.

5. The method for preparing nano copper metal wire for low temperature sintering conductive paste according to claim 4, characterized in that: In step (1), the mass ratio of the copper source, the reducing agent, the dispersing agent and deionized water is (5.545-55.45) g: (5.86-58.6) g: (7.85-70.63) g: (500-1500) g; the temperature of the hydrothermal reaction is 120-200° C., and the time of the hydrothermal reaction is 8-40 h.

6. The use of a nano copper metal material for low temperature sintering conductive paste as claimed in claim 1, characterized in that: Copper powder and organic carrier are prepared into conductive paste, which is used for bonding silicon carbide power device chips with DBC ceramic substrates or AMB copper substrates. The components and contents of the conductive paste are: 48-64wt% copper nanoparticles, 16-32wt% copper nanowires, 15wt% organic solvent, 4.5wt% small molecule organic copper salt, and 0.5wt% small molecule organic reagent.

7. The use according to claim 6, characterized in that: The organic solvent is one or more of dimethylformamide and dimethyl sulfoxide; the small molecule organic copper salt is one or more of copper formate and copper acetate; the small molecule organic reagent is one or more of formic acid and acetic acid; and the dissolution temperature is 40-150°C.

8. The use according to claim 6, characterized in that: The chip is bonded to the DBC ceramic substrate or the AMB copper substrate by printing a low-temperature sintering conductive paste on the copper substrate, and then the chip is placed on the other side of the paste, and then dried and sintered in sequence; wherein, the drying temperature is 100-140°C, and the time is 5-20 minutes; the sintering process is: in a nitrogen atmosphere, the temperature is increased to 275-350°C at a heating rate of 5-30°C / min and then kept warm for 20-60 minutes.

9. The use according to claim 8, characterized in that: The chip-bonding layer-DBC ceramic substrate or AMB copper substrate structure has a shear strength of up to 25MP, a thermal conductivity of up to 4W / m·K, and a densely sintered bonding layer.

Citation Information

Patent Citations

  • Synthesis of Copper Nanoparticles Using Rolling Ring Amplification Products as Templates and Their Application in Electrochemical Detection

    CN105567808B

  • Nanoparticle copper paste suitable for high-precision direct-writing 3D printing, preparation and application thereof

    CN113362984A

  • Preparation method of graphene-supported PtCu nano dendrite catalyst

    CN114068957A

Cited By

  • Composite copper paste for low-temperature sintering as well as preparation method and application of composite copper paste

    CN122575794A